Dasatinib induces fast and deep responses in newly diagnosed chronic myeloid leukaemia patients in chronic phase: clinical results from a randomised phase‐2 study (NordCML006). (13th September 2014) - Hjorth‐Hansen, Henrik; Stenke, Leif; Söderlund, Stina; Dreimane, Arta; Ehrencrona, Hans; Gedde‐Dahl, Tobias; Gjertsen, Bjørn Tore; Höglund, Martin; Koskenvesa, Perttu; Lotfi, Kourosh; Majeed, Waleed; Markevärn, Berit; et al.
Abstract We randomised 46 newly diagnosed patients with chronic myeloid leukaemia (median age 56) to receive dasatinib 100 mg QD or imatinib 400 mg QD and report outcome as an intention‐to‐treat analysis with 36 months follow‐up. Early cytogenetic and molecular responses were superior in the dasatinib group, with a tendency that imatinib patients caught up with time. For instance, MR3.0 was reached at 3 months in 36% vs. 8% (P = 0.02), at 12 months in 81% vs. 46% (P = 0.02) and at 18 months in 73% vs. 65% (n.s.) of the patients in the two groups. In contrast, MR4.5 was consistently superior in the dasatinib group at all time points from 6 months onwards, reaching 61% vs. 21% (P < 0.05) at 36 months. Sixty‐four vs. 71% of the patients in the dasatinib and imatinib arms, respectively, remained on assigned drug. Dasatinib dose was frequently reduced, but with maintained excellent effect. One imatinib patient progressed to blastic phase, but no CML‐related deaths occurred. In conclusion, our data compare favourably with those of the dasatinib registration study, DASISION. The fast and deep molecular responses induced by dasatinib compared with imatinib may be exploited to increase the proportion of patients who can achieve a treatment‐free remission after treatment discontinuation.